PERAN ETIKA BISNIS ISLAM PADA INDUSTRI RUMAHAN SEBAGAI PEDOMAN USAHA - M Iksan Purnama (Al-Amwal : Journal of Islamic Economic Law, 2019)
The role of Islamic business ethics in the home industry is a crucial aspect that is very important in every activity. As a guide in setting goals and ethical actions. As well as increasing consumer confidence in business people. This study aims to determine the role of Islamic business ethics in building Islamic business in home industry players. This article uses a qualitative research type with a descriptive approach. Business actors in the home industry who apply Islamic Business Ethics in their operations will get good feedback because the Islamic value applied will trust their consumers, thereby indirectly increasing income from their business.